(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Objective: Discuss the reinvention of Librarianship in the context of the fourth revolution. Methods: The study was characterized as descriptive and used literature review, bibliographic and documentary analysis as methods. Results: It presents an overview of the fourth revolution, promoted by digital technologies, and its impact on the world of work. It observes that, given the increasing ease of access to the internet, libraries are sharing their space as a provider of information sources and verifies the persistence of the librarian’s technical profile. It discusses the disconnect between higher education and the current and potential demands of the contemporary librarian’s job market in Brazil. Conclusions: It is recommended to rethink teaching in undergraduate librarianship and to promote continued learning so that librarians develop and update informational and technological skills.